Key principles to improve programmes and interventions in complementary feeding. Issue 3 (18th September 2013) - Lutter, Chessa K; Iannotti, Lora; Creed‐Kanashiro, Hilary; Guyon, Agnes; Daelmans, Bernadette; Robert, Rebecca; Haider, Rukhsana
Abstract: Although there are some examples of successful complementary feeding programmes to promote healthy growth and prevent stunting at the community level, to date there are few, if any, examples of successful programmes at scale. A lack of systematic process and impact evaluations on pilot projects to generate lessons learned has precluded scaling up of effective programmes. Programmes to effect positive change in nutrition rarely follow systematic planning, implementation, and evaluation (PIE) processes to enhance effectiveness over the long term. As a result a set of programme‐oriented key principles to promote healthy growth remains elusive. The purpose of this paper is to fill this gap by proposing a set of principles to improve programmes and interventions to promote healthy growth and development. Identifying such principles for programme success has three requirements: rethinking traditional paradigms used to promote improved infant and young child feeding; ensuring better linkages to delivery platforms; and, improving programming. Following the PIE model for programmes and learning from experiences from four relatively large‐scale programmes described in this paper, 10 key principles are identified in the areas of programme planning, programme implementation, programme evaluation, and dissemination, replication, and scaling up. Nonetheless, numerous operational research questions remain, some of which are highlighted in this paper.